Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/ceo.12500
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lapatinib and trastuzumab on vascular endothelial growth factor in experimental corneal neovascularization

Abstract: It is suggested that systemically administered lapatinib is more effective than systemically administered trastuzumab in preventing corneal neovascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
(90 reference statements)
0
11
0
Order By: Relevance
“…While a direct influence of lapatinib on blood flow was not reported in the literature, an anti-angiogenic effect in lung cancer xenografts and an anti-vascular effect in a rat model for corneal neovascularization has been reported following lapatinib administration, purportedly through downregulation of VEGF [52,53]. Thus, the reduced blood flow following lapatinib treatment at day 7 for the lapatinib only group may be indicative of its anti-angiogenic and anti-vascular properties.…”
Section: Discussionmentioning
confidence: 91%
“…While a direct influence of lapatinib on blood flow was not reported in the literature, an anti-angiogenic effect in lung cancer xenografts and an anti-vascular effect in a rat model for corneal neovascularization has been reported following lapatinib administration, purportedly through downregulation of VEGF [52,53]. Thus, the reduced blood flow following lapatinib treatment at day 7 for the lapatinib only group may be indicative of its anti-angiogenic and anti-vascular properties.…”
Section: Discussionmentioning
confidence: 91%
“…Oral administration of lapatinib reduced corneal epithelial and stromal VEGF expression, which correlated with decreased CoNV in a rat silver-nitrate CoNV model. Lapatinib was more effective at preventing CoNV than the large monoclonal antibody against HER2, trastuzumab [41].…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 92%
“…For example, the combination of dovitinib and bevacizumab was no more effective at reducing CoNV than bevacizumab monotherapy [45]. Additionally, lapatinib in combination with trastuzumab showed equivocal results to lapatinib monotherapy [41]. hesperetin and antiangiogenic effect of sunitinib are believed to be the contributing factors to a greater therapeutic effect than monotherapy.…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…In recent studies, both substances were compared for the treatment of experimental corneal angiogenesis. The results suggested that systemically administered lapatinib is more efective than systemically administered trastuzumab in preventing corneal angiogenesis [74].…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%